Synthesis and characterization of tin oxide thin films: A review - Ho, Soon Min (Scholars Research Library, 2016)
Tin oxide thin films have many advantages such as chemical inertness, high transparency, highly electrical conductive, and high temperature resistance. Up-to-date, numerous works have been reported by many scientists concerning SnO2 films using various deposition methods such as atmospheric pressure chemical vapour deposition method, electro deposition, chemical bath deposition, ultrasonic spray pyrolysis method, pulsed laser deposition method, magnetron sputtering method, and thermal evaporation method. The obtained films were investigated using different analysis tools such as x-ray diffractometer, scanning electron microscopy, UV-visible spectrophotometer and FTIR spectrometer. This study sought to elucidate the effects of the various deposition conditions on the morphological, structural, optical properties of SnO2 films.